2007
DOI: 10.1021/jp066388n
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Dynamics Study of a Nafion Polyelectrolyte Membrane and the Aqueous Phase Structure for Proton Transport

Abstract: A molecular dynamics simulation study of hydrated Nafion at water contents ranging from 5 to 20 wt % was performed to examine the structure and dynamics of the hydrated polyelectrolyte system. The simulations show that the system forms segregated hydrophobic regions consisting primarily of the polymer backbone and hydrophilic regions with an inhomogeneous water distribution. We find that the water clustering strongly depends on the water content. At low water content, only isolated small water clusters are for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
278
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(311 citation statements)
references
References 65 publications
28
278
5
Order By: Relevance
“…These results are in good agreement with experiments [18] and available MD results [53,54], and our multiscale approach better predicts compared to the full atomistic simulations [53,54], where the limited simulation size may not represent the domain-size-dependent water transport. With a consideration of hydration-dependent Nafion morphol-ogy (swelling), i.e., reduced domain sizes at low water activity, the water uptake is expected to decrease especially at the low water content, and this consideration results in better agreement with the experimental data.…”
Section: Water Self Diffusionsupporting
confidence: 87%
“…These results are in good agreement with experiments [18] and available MD results [53,54], and our multiscale approach better predicts compared to the full atomistic simulations [53,54], where the limited simulation size may not represent the domain-size-dependent water transport. With a consideration of hydration-dependent Nafion morphol-ogy (swelling), i.e., reduced domain sizes at low water activity, the water uptake is expected to decrease especially at the low water content, and this consideration results in better agreement with the experimental data.…”
Section: Water Self Diffusionsupporting
confidence: 87%
“…4). This is at variance with the work of Cui et al [68,69] who observed a less dispersed water distribution in Nafion as compared to Hyflon.…”
Section: Cluster Analysiscontrasting
confidence: 74%
“…25 Results of molecular modeling have been reported that give information relating the structure of the membrane with the mechanisms of proton conduction. 18,[33][34][35] Using MD simulation, Cui et al 36 studied the structure and dynamics of hydrated Nafion with water uptake ranging from 5 to 20 wt %. These authors found that at 5% the majority of the hydronium ions are hydrated by no more than two molecules of water, prohibiting structural diffusion.…”
Section: Introductionmentioning
confidence: 99%